Analisis Kualitas Pelayanan dalam Upaya Meningkatkan Penjualan Teh Botol Sosro dalam Kemasan Botol di PT Sinar Sosro Cabang Bandung - Ponco Riady, Reky; Tiris Sudrartono (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to analyze service quality as an effort to boost the sales of Teh Botol Sosro bottled drinks at PT Sinar Sosro's Bandung branch. The research results revealed a general increase in sales throughout 2022, albeit with monthly fluctuations influenced by factors such as season, promotions, product quality, and consumer preferences. Some issues, particularly a sales decline in September, require further analysis. The proposed solutions include in-depth data analysis, improved promotional strategies, better inventory management, understanding consumer preferences, a focus on product quality and service excellence, and collaboration with distributors. This research provides guidance for steps to enhance Teh Botol Sosro sales.